ENHANCEMENT OF CYBERSECURITY AWARENESS PROGRAM ON PERSONAL DATA PROTECTION AMONG YOUNGSTERS IN MALAYSIA: AN ASSESSMENT - Abd Rahim, Noor Hayani; Hamid, Suraya; Mat Kiah, Miss Laiha (Malaysian Journal of Computer Science, 2019)
Cybersecurity awareness program has been used as a medium to educate and make awareness among youngsters on personal data protection. However, it is still unclear the extent to which the effectiveness of this cybersecurity awareness program among youngsters require an assessment. This to ensure the current content of cybersecurity awareness program is consistently updated and aligned with current Internet usage among youngsters. Our assessment was systematically conducted using Kirkpatrick’s Four Learning Evaluation Model as conceptual framework; which consists of four phases of sequential assessment; Phase 1 –Reaction, Phase 2- Learning, Phase 3 – Behavior and Phase 4-Result. This study used mixed method research methodology in conducting the assessment and the instruments used in Phases 1 until 4 respectively were survey, pre-test and post-test survey, observation of web recording and focus group interview. The findings from this study revealed that youngsters do have positive reaction towards the program content, reported to have changes in terms of their knowledge and skills and practice of desired behavior on personal data protection. However, the undesired behavior also revealed practiced among youngsters and this suggest improvement required to the current module used to educate youngsters. The improvements include i) Decision making process in using personal data, ii) Management of online application iii)Management of online contents iv)Management of password and username. The result of this assessment is significant to the stakeholders in terms of providing insight into the effectiveness level of current module used to educate youngsters and assist them to decide better module.